Pharmacological screening of silibinin for antischizophrenic activity along with its acute toxicity evaluation in experimental animals - Ain, Qurat Ul; Saleem, Uzma; Ahmad, Bashir; Khalid, Iqra (Frontiers in Pharmacology, 2023)
Abstract Silibinin (SIL), a flavolignan extracted from medicinal plant ‘milk thistle’ has traditionally been used in treating liver disease. Now the phytochemical has already shown neuroprotective properties yet its activity against schizophrenia is still not elucidated. The present study was designed to evaluate the antipsychotic potential of silibinin and to probe its toxic potential. The acute oral toxicity study was assessed as per OECD 425 guidelines. Animals were divided into two groups of female rats (n=6); one group served as normal control and the other group received 2000 mg/Kg dose of SIL. In the current study, we further evaluated the antipsychotic potential of SIL. To this end, animals were divided into 6 groups (n=10) of mice for both the preventive and curative protocols. Group I (CMC 1 mL/Kg) served as normal control received CMC 1 mL/Kg, group II was diseased group treated with ketamine (10 mg/Kg) i.p, group III was standard group treated with clozapine 1 mg/Kg while group IV, V and VI have served as the treatment groups (receiving SIL 50, 100 and 200 mg/Kg respectively) by oral route for both the protocols. Improvement in positive symptoms of disease was evaluated by stereotypy and hyperlocomotion whereas negative symptoms (behavioral despair) were determined by forced swim test and tail suspension test in mice models. Results suggested that the LD50 of SIL was greater than 2000 mg/Kg. Moreover, SIL has prevented and reversed ketamine induced increase in stereotypy (P<0.001) and behavioral despair in forced swim and tail suspension tests (P<0.001). Taken together, the findings suggest that silibinin is a safe drug with low toxicity potential and has demonstrated significant antipsychotic activity against positive and negative symptoms of schizophrenia.